2013
DOI: 10.1016/j.jtrangeo.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Foreland determination for containership and general cargo ports in Europe (2007–2011)

Abstract: Abstract. A simple and accurate relationship is demonstrated that links the average shortest path, nodes, and edges in a complex network. This relationship takes advantage of the concept of link density and shows a large improvement in fitting networks of all scales over the typical random graph model. The relationships herein can allow researchers to better predict the shortest path of networks of almost any size.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Some of them discussed the effect of node aggregation at different scales (Tsiotas and Polyzos, 2018;Wang et al, 2019a), while others studied the global maritime network with the world region as the unit of analysis (Tran and Haasis, 2014;Li et al, 2015;Xu et al, 2015). A large body of literature focused on ranking ports by centrality indicators, introducing more or less novelty (Wang and Cullinane, 2008;Lam and Yap, 2011;Montes et al, 2012;Cullinane and Wang, 2012;Doshi et al, 2012;Freire Seoane et al, 2013;Wang and Cullinane, 2014;Kang et al, 2014;Bartholdi et al, 2016). Certain works, albeit not always referring to "complex networks" explicitly, pushed the analysis of port centrality one step further, by examining the interrelation between centrality and actual port throughput (Kim and Lu, 2015;Wang and Cullinane, 2016;Kang and Woo, 2017), combining network analysis with multiple regression and data envelopment analysis.…”
Section: From Graph Theory To Complex Networkmentioning
confidence: 99%
“…Some of them discussed the effect of node aggregation at different scales (Tsiotas and Polyzos, 2018;Wang et al, 2019a), while others studied the global maritime network with the world region as the unit of analysis (Tran and Haasis, 2014;Li et al, 2015;Xu et al, 2015). A large body of literature focused on ranking ports by centrality indicators, introducing more or less novelty (Wang and Cullinane, 2008;Lam and Yap, 2011;Montes et al, 2012;Cullinane and Wang, 2012;Doshi et al, 2012;Freire Seoane et al, 2013;Wang and Cullinane, 2014;Kang et al, 2014;Bartholdi et al, 2016). Certain works, albeit not always referring to "complex networks" explicitly, pushed the analysis of port centrality one step further, by examining the interrelation between centrality and actual port throughput (Kim and Lu, 2015;Wang and Cullinane, 2016;Kang and Woo, 2017), combining network analysis with multiple regression and data envelopment analysis.…”
Section: From Graph Theory To Complex Networkmentioning
confidence: 99%
“…Maritime traffic has been mapped using AIS data with respect to ports in just a few papers. Seoane et al [40] determined the foreland of container and general cargo ports in Europe; Jia et al [41] investigated Norwegian port connectivity in terms of vessel visits, vessel sizes, and cargo sizes; Yu et al [42] showed the different layers that Chinese ports are linked in and; based on the use of AIS data, Jia et al [43] proposed an algorithm for aggregating, mapping and distributing real-time trade flows between the major ports of the world. There has been even less port-based research using AIS data that has focussed on areas that are more directly relevant to the objectives of this paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In these studies, the hierarchy is not based on the volume of traffic handled at the ports but on their position in the network. The most common network indicators used for the ranking of ports are degree centrality (number of connections of a port) in order to assess its connectivity and betweenness centrality (number of shortest paths between any pair of ports in the network that pass through a specific port) in order to evaluate how centrally is a port placed in the network (Cisic et al, 2007;Ducruet et al, 2009b;Ducruet et al, 2010b;Ducruet and Notteboom, 2012a,b;Gonzalez et al, 2012;Pais-Montes et al, 2012;Freire et al, 2013;Tovar et al, 2015;Ducruet, 2013a,b;Kang and Woo, 2017).…”
Section: Formation Of Hierarchies In Empirical Applicationsmentioning
confidence: 99%
“…• To identify how ports are positioned in maritime networks, global or regional (Cisic et al, 2007;Ducruet et al, 2009b;Ducruet et al, 2010b;Ducruet and Notteboom, 2012a,b;Gonzalez et al, 2012;Pais-Montes et al, 2012;Freire et al, 2013;Tovar et al, 2015;Ducruet, 2013a,b;Kang and Woo, 2017). The most common indicators that are used are the degree (number of connections of a port) in order to assess its connectivity and the betweenness centrality (number of shortest paths between any pair of ports in the network that pass through a specific port) in order to evaluate how centrally is a port placed in the network.…”
Section: Literature Reviewmentioning
confidence: 99%